Adaptation of steppe plant species in technogenic ecotopes of the South-East of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
Species composition of steppe plants (85 species) and their spread in different types of technogenic ecosystems in the South-East of Ukraine have been studied. When studying the population structure of a steppe species-edifier Festuca valesiaca Gaudin. in a mine dump ecotope we have established the age spectrum and density of this population species, being close to those of this species populations growing under conditions of a regulated grazing. We have made an inventory and bioecological classification of steppe plants belonging to the natural flora and have analyzed these plants’ distribution in technogenic ecosystems. These efforts enabled us to define a range of tolerant, meliorative, ornamental and other species fit for the purposes of propagation in urban and man disturbed areas. The methods of optimization of technogenic, urbanized territories and industrial sites using steppe plant species of natural flora, taking into account their bioecological potential and tolerance to anthropogenic factor are recommended.
Keywords: steppe plants, technogenic ecosystems, industrial sites, urban areas, the South- East of Ukraine.